2012
DOI: 10.5603/fhc.2012.0052
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in HeLa cells upon imperatorin and cisplatin treatment

Abstract: Abstract:There is growing evidence that commonly applied chemotherapy regimens can be improved by introducing new, specific, active and low side-effect drugs, or by combining substances to obtain the required clinical effect. The aim of the present study was to investigate the effects of imperatorin and cisplatin, applied separately or in combination, on apoptosis, necrosis and autophagy induction in the human cervical carcinoma cell line (HeLa). Imperatorin appeared to be a potent autophagy inducer, rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Therefore, it is extremely important to search for new bioactive substances of plant origin that can increase the effectiveness and reduce the systemic toxicity observed during anticancer treatment. Therefore, in cancer therapy, attention is paid to natural substances [ 45 , 46 , 47 , 48 , 49 , 50 ], and numerous studies have confirmed the effectiveness of furanocoumarins in anticancer therapy, including multidrug-resistant (MDR) cancers, for which no ideal treatment is available at present [ 46 , 51 , 52 ]. For example, bergapten and xanthotoxin were found to have cytotoxicity against gastric (EPG85.257RDB), ovarian (A2780RCIS), and breast cancer (MCF7MX) cell lines overexpressing multidrug-resistant proteins (MDR1, MRP2, and BCRP) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is extremely important to search for new bioactive substances of plant origin that can increase the effectiveness and reduce the systemic toxicity observed during anticancer treatment. Therefore, in cancer therapy, attention is paid to natural substances [ 45 , 46 , 47 , 48 , 49 , 50 ], and numerous studies have confirmed the effectiveness of furanocoumarins in anticancer therapy, including multidrug-resistant (MDR) cancers, for which no ideal treatment is available at present [ 46 , 51 , 52 ]. For example, bergapten and xanthotoxin were found to have cytotoxicity against gastric (EPG85.257RDB), ovarian (A2780RCIS), and breast cancer (MCF7MX) cell lines overexpressing multidrug-resistant proteins (MDR1, MRP2, and BCRP) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that isopimpinellin affected PI3K activity and, consequently, neutrophil motility during the recruitment phase of inflammation. Additionally, some furanocoumarins have been reported to have chemotherapeutic synergistic potential when applied in combination with other anti-tumor drugs [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding indicated that cisplatin induced cell death through apoptosis and necrosis pathway. 36 Another significant feature of a potential anticancer agent is its ability to induce cell cycle arrest. The molecular mechanism underlying Pharmacognosy Journal, Vol 13, Issue 2, Mar-Apr, 2021 a compound's cytotoxicity can be understood from the cell cycle analysis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, HSP90 was also observed to be present in control cells owing to its natural expression in a variety of cancers. 35 In comparison to 2D cultures, higher expression of HSPs on HS exposure in 3D models suggests that cells in the 3D cultures are better able to mimic the actual TME. 36 Thereby, justifying the lesser cell death in 3D models as compared to 2D as reported in our study.…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 97%